Optional CMOS based Monolithic Light Sensor for Detection of Light Intensity - Kean, Woon Yun; Mat Jubadi, Warsuzarina; Ahmad, Nabihah@Nornabihah (International Journal of Integrated Engineering, 2020)
Conventional light intensity sensing devices such as a light meter are big in size and incapable of outputting a digitized signal to a microprocessor for further control and actuation. Sensor transducers based on CMOS has therefore increased in popularity. Using CMOS technology, manufacturing costs and the power consumption can be reduced with smaller form factor. This paper presents a proposed design of light sensor for the detection of light intensity. The project utilizes Silterraâ€™s 130 nm CMOS architecture to create a low power and low space monolithic light sensor chip that is able to detect the intensity of light to assist in achieving the recommended levels of light intensity in domestic areas. The light intensity was simulated with a photocurrent and the photodiode operates optimally at a wavelength of 555 nm, the spectral sensitivity of the human eye and has good linearity. The light intensity detected is shown in illuminance (lux) and this project is capable to detect illuminance in the range of 0 to 200 lux with a resolution of 20 lux. The monolithic chip of the light intensity sensor comprises of the transimpedance amplifier which acts as a current to voltage converter and an ADC to convert the analog voltage into a digital reading.  Hence, the output of the light intensity sensor is in binary representation.  The total power consumption of the monolithic light intensity sensor is 1.88mW and the total size of the design is 0.01202 mm2.